2004
DOI: 10.1242/jcs.01529
|View full text |Cite
|
Sign up to set email alerts
|

LAP2α and BAF transiently localize to telomeres and specific regions on chromatin during nuclear assembly

Abstract: Lamina-associated polypeptide (LAP) 2α is a LEM (lamina-associated polypeptide emerin MAN1) family protein associated with nucleoplasmic A-type lamins and chromatin. Using live cell imaging and fluorescence microscopy we demonstrate that LAP2α was mostly cytoplasmic in metaphase and associated with telomeres in anaphase. Telomeric LAP2α clusters grew in size, formed `core' structures on chromatin adjacent to the spindle in telophase, and translocated to the nucleoplasm in G1 phase. A subfraction of lamin C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
206
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 188 publications
(227 citation statements)
references
References 82 publications
19
206
0
Order By: Relevance
“…In support of this, it has been shown that lamins interact with mitotic chromosomes (32)(33)(34) and that their assembly at the surface of chromosomes is crucial for postmitotic nuclear formation (35,36). It is also possible that the E145K mutation interferes with the lamin binding to matrix attachment regions of DNA (37) or interactions with other chromatin associated lamin-binding proteins such as histones, LAP2␣, BAF (33), and/or SUN2 (38). Even though we do not know the exact mechanisms responsible for the impact of the E145K mutation, the results of this study provide important insights into the role of lamins in the spatial and temporal organization of chromosomes throughout the cell cycle.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In support of this, it has been shown that lamins interact with mitotic chromosomes (32)(33)(34) and that their assembly at the surface of chromosomes is crucial for postmitotic nuclear formation (35,36). It is also possible that the E145K mutation interferes with the lamin binding to matrix attachment regions of DNA (37) or interactions with other chromatin associated lamin-binding proteins such as histones, LAP2␣, BAF (33), and/or SUN2 (38). Even though we do not know the exact mechanisms responsible for the impact of the E145K mutation, the results of this study provide important insights into the role of lamins in the spatial and temporal organization of chromosomes throughout the cell cycle.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, the expression of LA/C with the E145K mutation inhibits the normal reorganization of interphase chromosome territories in daughter cells in early G1, most likely due to the formation of an abnormal lamina structure. In support of this, it has been shown that lamins interact with mitotic chromosomes (32)(33)(34) and that their assembly at the surface of chromosomes is crucial for postmitotic nuclear formation (35,36). It is also possible that the E145K mutation interferes with the lamin binding to matrix attachment regions of DNA (37) or interactions with other chromatin associated lamin-binding proteins such as histones, LAP2␣, BAF (33), and/or SUN2 (38).…”
Section: Discussionmentioning
confidence: 97%
“…Oligomeric Complexes in Vivo-Our previous studies revealed the formation of stable, chromatin-associated LAP2␣ structures during early nuclear assembly stages (14,17), indicating oligomerization of the protein. To analyze oligomeric LAP2␣ structures in vivo and to determine the domain of LAP2␣ responsible for oligomerization, either full-length LAP2␣ or the LAP2␣-specific C-terminal domain, LAP2␣-(188 -693), fused to the C terminus of monomeric red fluorescent protein 1 (mRFP1) (Fig.…”
Section: The C Terminus Of Lap2␣ Is Involved In the Formation Ofmentioning
confidence: 95%
“…The LAP2␣-lamin A/C-pRb complex is thought to regulate cell proliferation and differentiation in adult stem cells (3,12). During mitosis, LAP2␣ dissociates from chromosomes in a phosphorylation-dependent manner and is redistributed throughout the mitotic cytoplasm, like most nuclear lamina components (14,15). However, during anaphase, LAP2␣ associates with the telomeres of separated sister chromatids and subsequently forms stable structures associated with decondensing chromatin before the nuclear envelope is formed (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation